ГИДРАВЛИЧЕСКАЯ МОДЕЛЬ ДЛЯ УСТАНОВЛЕНИЯ КОЭФФИЦИЕНТА ШЕРОХОВАТОСТИ В МЕЛИОРАТИВНОЙ ПРАКТИКЕ - Авлакулов, Мейли (Innovatsion texnologiyalar, 2022)
The article deals with the modeling of surface water dynamics in shallow water models. When irrigating crops along furrows, in the process of movement of shallow water along the irrigation furrow, erosion or silting occurs, depending on the shape of the bottom of the furrow. On the lysimetric complex, the nature of the movement of shallow water was studied, and on the basis of studying them, a hydraulic model was compiled according to the influence of hydraulic resistance in the form of the roughness of the bottom of the furrow. When compiling the model, the classical methods of Manning, Pavlovsky and Darcy–Weisbach were used.